Analisis Total Productive Maintenance Pada Mesin Las Semi Robotik Dengan Pendekatan Metode Overall Equipment Effectiveness di PT Refindo Intiselaras - Ichwannudin, Rifqi Wahyu; Muttaqin, Aan Zainal; Susanto, Doni (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the implementation of Total Productive Maintenance (TPM) on the Semi Robotic Welding Machine at PT Refindo Intiselaras using the Overall Equipment Effectiveness (OEE) approach to find the causes of high downtime. This study took place from January to December 2024 using data on the three main components of OEE: Availability, Performance, Quality. The analysis showed that the average value of Availability was 95.30%, Performance was 89.47%, and Quality was 99.07%, with the average OEE value reaching 84.47%. This figure has not met the international OEE standard set at 85%, with the main factors that hinder it being variations in Performance as well as a small decrease in Quality. It is recommended that the company improve supervision of machine operational speed and strengthen the implementation of TPM between divisions to achieve maximum yield value in the production process.